THE ROLE OF SYNTACTICAL STYLISTIC DEVICES IN FAIRY TALES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the use of syntactical stylistic devices in fairy tales, emphasizing their significance in enhancing narrative structure and engaging readers. Key devices such as repetition, parallelism, enumeration, inversion, polysyndeton, asyndeton, and ellipsis are analyzed to demonstrate how they contribute to the rhythmic flow, emotional tone, and thematic depth of the tales. The analysis illustrates how these syntactical structures aid in memory retention, enhance the magical quality of the stories, and reflect deeper cultural meanings. Through this examination, the article underscores the timeless appeal of fairy tales and the integral role of syntax in shaping their enduring charm.